Analysis of the patients' quality of life after radical cystectomy with the orthotopic neobladder or ileal conduit formation - S. V. Kotov; A. L. Khachatryan; D. P. Kotova; A. K. Zhuravleva; Sh. M. Sargsyan; D. M. Magomedov (Вестник урологии)
Introduction. Orthotopic neobladder or ileal conduit are the most optimal and common methods of intestinal urine diversion. Nevertheless, there is no consensus in the current literature as to which of these urine diversion techniques provides a better quality of life.Purpose of the study. To conduct a comparative study of the quality of life of patients who underwent radical cystectomy with the formation of an orthotopic neobladder or ileoconduit.Materials and methods. The study included 60 patients (46 men (76.6%) and 14 (23.4%) women) who underwent radical cystectomy (RCE) with intestinal urine diversion. The mean age of the patients was 66 (47 - 85) years. The exclusionary criteria for the study were: neoadjuvant chemotherapy for bladder cancer; preoperative ASA IV - V degree; RCE with intestinal urine diversion not for bladder cancer; the inability to fill out questionnaires assessing the postoperative aspects of the quality of life (QoL) for certain reasons. All patients were divided into 2 groups to allow comparative analysis: Group I — 26 patients (43.3%) underwent RCE with the formation of an orthotopic neobladder according to the Studer method; Group II — 34 patients (56.7%) underwent RCE with the formation of an ileal conduit according to Bricker. The median follow-up period for patients from the completed surgical procedure to the survey was 7 months (4.5 - 9.5 months). The monitoring of the postoperative patients' QoL after RCE was carried out based on the questionnaires: EORTC QLQ-C30, EORTC QLQ-BLM. Also, we carried out a retrospective comparative analysis of early postoperative complications and mortality after RCE in both groups due to Clavien-Dindo classification.Results. The mean time of surgery in Groups I was 280 ± 56.3 min, in Group II — 230 ± 60.8 minutes, (p = 0.117), median blood loss was 350 ml (283 - 380) in Group 1 with 270 (245 - 310) ml in Group 2 (p = 0.213). The frequency of complications according to Clavien-Dindo I - II in the Group 1 was observed in 11 (42.3%) patients, in the Group 2 in 12 (35.2%) patients (p = 0.579), complications according to Clavien-Dindo III - IV in the Group 1 were found in 5 (19.2%) patients while in the Group 2 in 7 (20.5%) patients (p = 0.896). The mortality rate was 8.3% (5 people) and there is no statistically significant difference in the mortality rate in both groups of patients (p = 0.241). Based on the analysis of the QLQ-C30 and QLQ-BLM questionnaire data, we noted that a total of «good» quality of life in the Group 1 was noted by up to 18 (69.2%) patients compared with the Group 2 in up to 15 (44.1%) patients (p < 0.05). At the same time, the predominance of the QoL was observed on all the main scales of the QLQ-C30 questionnaire: the scale of physical condition, cognitive functions, emotional state and social adaptation. According to the results of the QLQ-C30 questionnaire, there were more financial in the group of patients with an ileal conduit. In the postoperative period, the following symptoms prevailed in both groups of patients: nausea, vomiting, weakness and pain. During the analysis of the functional results, we noted that in Group I,4 (15.3%) patients had nocturnal and daytime urinary incontinence, 2 (7.6%) patients required self-catheterization of the intestinal reservoir periodically, in Group II — 8 (23.5%) patients report urine leakage from the urostomy and skin dermatitis periodically.Conclusion. Despite the fact of worldwide recognition as a result of the preferences of surgeons in favour of the ileal conduit formation by the Bricker technique during RCE, urine diversion using orthotopic neobladder demonstrates better results with analysis of QoL in our patients. Obviously, long-term studies with a large sample of patients are required to obtain more reliable results of a QoL evaluation after RCE with intestinal urine diversion.